2023
DOI: 10.3389/fphar.2023.1101240
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the molecular mechanism of notoginsenoside R1 in sepsis-induced cardiomyopathy based on network pharmacology and experiments validation

Abstract: Sepsis-induced cardiomyopathy (SIC) is an important manifestation of sepsis, and abnormal cardiac function affects the development of sepsis. Notoginsenoside R1 (NG-R1) is a unique bioactive component of Panax notoginseng with anti-inflammatory and antioxidant effects. However, the effects and possible mechanisms of NG-R1 on SIC are not clear. The purpose of this study was to identify the potential targets and regulatory mechanisms of the action of NG-R1 on SIC. To investigate the potential mechanism, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Notoginsenoside R1 is a bioactive compound that was isolated from Sanqi and has been extensively studied for its various therapeutic properties, including anti-inflammatory and anti-oxidative effects. 33 However, its clinical applications are limited owing to low bioavailability and poor solubility. Therefore, several studies have explored the transformation of notoginsenoside into its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Notoginsenoside R1 is a bioactive compound that was isolated from Sanqi and has been extensively studied for its various therapeutic properties, including anti-inflammatory and anti-oxidative effects. 33 However, its clinical applications are limited owing to low bioavailability and poor solubility. Therefore, several studies have explored the transformation of notoginsenoside into its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-α, as a major regulator of the infammatory response, has been proposed to be a key contributing factor in septic cardiomyopathy. It was reported that the early depression of contractility was largely due to LPS-induced TNF-α synthesis [33], and TNF-α was suggested to be the core target of anti-infammation in septic cardiomyopathy [34].…”
Section: Infammationmentioning
confidence: 99%